Influence of self-esteem, psychological empowerment, and empowering leader behaviors on assertive behaviors of staff nurses - Ryan Michael F Oducado (Belitung Nursing Journal, 2021)
Background: Being assertive is essential skill nurses need to learn and develop. While many studies exist on nurses’ assertiveness, there is limited research on the factors associated with Filipino nurses’ assertive behaviors. Objective: This study examined the correlation of self-esteem, psychological empowerment, and leader empowering behaviors on staff nurses’ assertiveness in the workplace. Methods: This cross-sectional study conducted in 2019 involved 223 staff nurses working in two tertiary hospitals in the Philippines. Data were gathered using four validated self-reported scales: self-esteem scale, psychological empowerment scale, leader empowering behavior questionnaire, and workplace assertive behavior questionnaire. Correlational analysis using Pearson’s r was performed to test the relationship between the key variables. Results:  The composite scores for the self-esteem, psychological empowerment, empowering leader behaviors, and workplace assertiveness were 32.06 (SD = 3.65), 4.22 (SD = 0.43), 3.86 (SD = 0.51) and 3.61 (SD = 0.55), respectively. Self-esteem (r = 0.216; p = 0.001), psychological empowerment (r = 0.455, p = 0.000), and empowering leader behaviors (r = 0.269; p = 0.000) were significantly correlated with staff nurses’ assertiveness in the workplace. Conclusion: Self-esteem, nurse leadership behaviors, and empowerment play vital roles in staff nurses’ assertiveness. Understanding the factors influencing nurses’ assertiveness is important, and looking into these variables can be beneficial for nursing management when developing strategies to build nurses’ assertiveness. Thus, it is vital to focus on helping nurses nurture healthy self-esteem and initiate empowering conditions at work to aid nurses in setting healthy boundaries and supporting assertive behaviors at work.